Optimal parameter determination of repetitive transcranial magnetic stimulation for treating treatment-resistant depression: A network meta-analysis of randomized controlled trials - Li, Jinbiao; Cui, Liqian; Li, Hao (Frontiers in Psychiatry, 2022)
Background Many studies have shown the efficacy of repetitive transcranial magnetic stimulation (rTMS) in treatment-resistant depression (TRD). However, the choice of different parameters has been a challenging issue. Methods PubMed, Cochrane, and Embase databases were searched for relevant studies until June 20, 2022. The treatment efficacy was evaluated by the relative risk (RR) using the pairwise test for response and remission rates. Subgroup and sensitivity analyses were conducted to explore the primary outcome differences and to assess the reliability of the results. Results Thirty-seven trials comprising 2120 participants with TRD were included. The more efficacious interventions compared to sham controls included high-frequency left followed by low-frequency right sup-threshold (HFL-LFR-sup-rTMS, RR = 5.29, 95% CI: 1.24–22.50), high-frequency left sup-threshold (HFL-sup-rTMS, RR = 2.97, 95% CI: 1.74–5.05), low-frequency right sup-threshold (LFR-sup-rTMS, RR = 2.72, 95% CI: 1.50–4.90), low-frequency right followed by high-frequency left sup-threshold (LFR-HFL-sup-rTMS, RR = 2.71, 95% CI: 1.62–4.53), and high-frequency left sub-threshold (HFL-sub-rTMS, RR = 1.91, 95% CI: 1.18–3.10) rTMS. The estimated relative ranking of treatments suggested that HFL-LFR-sup-rTMS (84.4%) might be the most efficacious among all rTMS strategies. No treatments showed a lower acceptability than the sham control. Limitations Subgroup analysis was not conducted to compare the efficacy of rTMS treatment between bipolar and unipolar depression, and small-study effects possibly introduced bias. Conclusion Treatment with HFL-LFR-sup-rTMS, HFL-sup-rTMS, LFR-sup-rTMS, LFR-HFL-sup-rTMS, or HFL-sub-rTMS is more efficacious than the sham control. HFL-LFR-sup-rTMS and HFL-sup-rTMS may be the two best among the most efficacious rTMS treatments. Systematic review registration [https://www.crd.york.ac.uk/PROSPERO], identifier [CRD42022334481].